2022
DOI: 10.1186/s11658-021-00305-5
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of canonical Wnt/β-catenin signaling with protein lysine acetylation

Abstract: Canonical Wnt/β-catenin signaling is a complex cell-communication mechanism that has a central role in the progression of various cancers. The cellular factors that participate in the regulation of this signaling are still not fully elucidated. Lysine acetylation is a significant protein modification which facilitates reversible regulation of the target protein function dependent on the activity of lysine acetyltransferases (KATs) and the catalytic function of lysine deacetylases (KDACs). Protein lysine acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 99 publications
(105 reference statements)
0
18
1
Order By: Relevance
“…CSNK1D was discovered to potentially interact with DVLs via proteinprotein interaction (PPI) prediction. The DVLs interactome is a well-known regulator of the Wnt pathway, which facilitate inhibition of the destruction complex targeting β-catenin at the cell membrane [39,40]. According to the experimental validation, knockdown of CSNK1D could only inhibit the expression of DVL3 rather than DVL1 or DVL2.…”
Section: Discussionmentioning
confidence: 99%
“…CSNK1D was discovered to potentially interact with DVLs via proteinprotein interaction (PPI) prediction. The DVLs interactome is a well-known regulator of the Wnt pathway, which facilitate inhibition of the destruction complex targeting β-catenin at the cell membrane [39,40]. According to the experimental validation, knockdown of CSNK1D could only inhibit the expression of DVL3 rather than DVL1 or DVL2.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between lysine acetylation and Wnt/β-catenin signaling pathway is of great significance to the occurrence and progression of tumors. Histone lysine acetylation can regulate the transcription of important biomolecules in the Wnt/β-catenin signaling pathway, while non-histones Lysine acetylation directly alters the function of core molecules in Wnt/β-catenin signaling pathway [36]. Previous studies have shown that the Wnt/β-catenin signaling pathway plays an important role in the occurrence and progression of osteosarcoma [37,39].…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of Wnt and receptor leads to Axin and Disheveled proteins being recruited to the cell membrane and inhibits glycogen synthase kinase (GSK)-3β protein. β-Catenin can trigger GSK-3β to negatively regulate the Wnt pathway [ 34 36 , 42 , 43 ]. Notably, GSK-3β inhibition causes accumulation of β-catenin in the cytoplasm and paves the way for its translocation into the nucleus.…”
Section: Major Signaling Pathways In Breast Cancermentioning
confidence: 99%